Spatial heterogeneity accelerates phase-to-trigger wave transitions in frog egg extracts - Owen Puls; Daniel Ruiz-Reynés; Franco Tavella; Minjun Jin; Yeonghoon Kim; Lendert Gelens; Qiong Yang (Nature Communications, 2024)
Abstract Cyclin-dependent kinase 1 (Cdk1) activity rises and falls throughout the cell cycle: a cell-autonomous process called mitotic oscillations. Mitotic oscillators can synchronize when spatially coupled, facilitating rapid, synchronous divisions in large early embryos of Drosophila (~0.5 mm) and Xenopus (~1.2 mm). Diffusion alone cannot achieve such long-range coordination. Instead, studies proposed mitotic waves—phase and trigger waves—as mechanisms of the coordination. How waves establish over time remains unclear. Using Xenopus laevis egg extracts and a Cdk1 Förster resonance energy transfer sensor, we observe a transition from phase to trigger wave dynamics in initially homogeneous cytosol. Spatial heterogeneity promotes this transition. Adding nuclei accelerates entrainment. The system transitions almost immediately when driven by metaphase-arrested extracts. Numerical simulations suggest phase waves appear transiently as trigger waves take time to entrain the system. Therefore, we show that both waves belong to a single biological process capable of coordinating the cell cycle over long distances.